Упростите выражение: а) 5 а+7 б-2 а-8 бб) 3 (4 х+2) - 5 в) 20 б - (б-3) + (3 б-10)

0
Ответы (2)
  1. 8 июля, 06:09
    0
    A)

    5 а + 7b - 2 а - 8b = a (5 - 2) + b (7 - 8).

    Б)

    3 (4 х + 2) - 5 = 12x + 6 - 5 = 12x + 1.

    B)

    20b - (b - 3) + (3b - 10) = 20b - b + 3 + 3b - 10 = 22b - 7.

    Удачи в решении)))
  2. 8 июля, 07:00
    0
    а) 5 а+7 б-2 а-8 б=3 а-7 б-8 б=3 а-15 б=3 (а+5 б)

    б) 3 (4 х+2) - 5=12 х+6-5=12 х+1

    в) 20 б - (б-3) + (3 б-10) = 20 б-б+3+3 б-10=22 б+3-10=22 б-7
Знаешь ответ на этот вопрос?